Effect of Sodium Chloride on Photosynthetic Pigments and Photosynthetic Characteristics of Avicennia Officinalis Seedlings - R. Ranganathan2, and P. Anantharaman3, R. Saravanavel1 (Recent Research in Science and Technology, 2011)
The possible effect of salinity (0,-2.00% NaCl) on chlorophyll pigment content and photosynthetic activity of Avicennia officinalis L. were investigated. The seedlings of this species treated with NaCl above 2.00% and could not survive a month after salt treatment. The maximum accumulation of chlorophyll synthesis was observed at 0.75% NaCl, beyond this level is reduced gradually. The rate of photosynthetic activity significantly enhanced up to optimum level of 0.75% NaCl and at higher concentrations the photosynthetic activity were reduced.